2016
DOI: 10.1111/jog.12993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti‐β2‐GPI antibodies on cytokine production in normal first‐trimester trophoblast cells

Abstract: We suspect that aβ2-GPIAb might increase cytokine production by binding to TLR2 or TLR4. The increased cytokine production in response to aβ2-GPIAb might play a role in the increased inflammatory response in the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Serum IL-8 levels were also higher in those with severe versus mild pre-eclampsia (29). Although we saw no correlation of aPL with pregnancy morbidity in our patients, recent in-vitro studies have shown that aPL can induce IL-8 and IL-6 secretion in trophoblasts (30). Vitamin D treatment alone or in combination with low molecular weight heparin has also been shown to attenuate the aPL-mediated proinflammatory response in trophoblast cultures (31).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Serum IL-8 levels were also higher in those with severe versus mild pre-eclampsia (29). Although we saw no correlation of aPL with pregnancy morbidity in our patients, recent in-vitro studies have shown that aPL can induce IL-8 and IL-6 secretion in trophoblasts (30). Vitamin D treatment alone or in combination with low molecular weight heparin has also been shown to attenuate the aPL-mediated proinflammatory response in trophoblast cultures (31).…”
Section: Discussioncontrasting
confidence: 86%
“…29 Although we saw no correlation of aPL with pregnancy morbidity in our patients, recent in vitro studies have shown that aPL can induce IL-8 and IL-6 secretion in trophoblasts. 30 Vitamin D treatment alone or in combination with low molecular weight heparin has also been shown to attenuate the aPL-mediated proinflammatory response in trophoblast cultures. 31 It should be noted, however, that while currently available clinical evidence indicates no association between hypovitaminosis D and obstetric APS manifestations, a recent cross-sectional study of women with recurrent pregnancy loss reported an association between low vitamin D levels and increased odds of positive aPL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of obstetric APS have also yielded mixed results with an older study demonstrating no role for TLR4 in an in vivo model of pregnancy loss [35]. In contrast, Azuma and colleagues recently suggested that, at least in vitro, TLR2 and TLR4 facilitate inflammatory cytokine production by trophoblast cells in response to anti-β 2 GPI antibodies [36]. …”
Section: Cell Activation and Signaling Pathways: New Conceptsmentioning
confidence: 99%
“…When the antiphospholipid antibody binds to β 2 GPI, the antibody complex interacts with a number of receptors, like annexin A2, Toll‐like receptor family, glycoprotein Ibα, low‐density lipoprotein receptor‐related protein 8 and low‐density lipoprotein receptor family. The result is the activation of endothelial cells, platelets, monocytes, 7 and trophoblasts 8,9 . The inflammation and clotting that follow could lead to vascular thrombosis or pregnancy‐related complications 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…The result is the activation of endothelial cells, platelets, monocytes, 7 and trophoblasts. 8,9 The inflammation and clotting that follow could lead to vascular thrombosis or pregnancyrelated complications. 10,11 On β 2 GPI, the domain I is the antigenic epitope specifically bound by the antiphospholipid antibody.…”
Section: Introductionmentioning
confidence: 99%